Optimizing The MPLS Support For Real Time IPv6-Flows Using MPLS-PHS Approach. - Tat, Chee Wan; Alzyoud, Faisal Y.; Sumari, Putra (2009)
The huge coverage space of IPv6 addresses and providing guaranteed support for the ever increasing customer demand, results in the dealing with bigger packet header-size compared to the payload-size especially in some real time video and audio applications, consequently more bandwidth is wasting.